2006
DOI: 10.1002/dvdy.21000
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 and Notch2 receptors influence progressive hair graying in a dose‐dependent manner

Abstract: The Notch signaling pathway is involved in diverse biological processes such as cell fate decisions or stem cell maintenance. In this study, we assessed the role of this pathway for melanocyte development and hair pigmentation using RBP-J, Notch1, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 36 publications
2
116
1
1
Order By: Relevance
“…We used mice carrying floxed alleles of RBP-Jk Tanigaki et al, 2002) and Notch2 (Besseyrias et al, 2007), which is the main Notch receptor expressed in the RPE (Bao and Cepko, 1997), but included mice with floxed Notch1 (Radtke et al, 1999) because of its significant role in the neural crestderived pigment cell lineage (Schouwey et al, 2007). These mice were bred with mice expressing the Cre recombinase under the control of the tyrosinase-related protein 1 (Tyrp1) promoter (Mori et al, 2002).…”
Section: Disruption Of Notch Signaling In Rpe Cells Results In a Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…We used mice carrying floxed alleles of RBP-Jk Tanigaki et al, 2002) and Notch2 (Besseyrias et al, 2007), which is the main Notch receptor expressed in the RPE (Bao and Cepko, 1997), but included mice with floxed Notch1 (Radtke et al, 1999) because of its significant role in the neural crestderived pigment cell lineage (Schouwey et al, 2007). These mice were bred with mice expressing the Cre recombinase under the control of the tyrosinase-related protein 1 (Tyrp1) promoter (Mori et al, 2002).…”
Section: Disruption Of Notch Signaling In Rpe Cells Results In a Micrmentioning
confidence: 99%
“…In contrast to other organs, the implication of the Notch signaling pathway has only been recently addressed in the pigmentary system (Schouwey and Beermann, 2008), and mouse and human melanocytes have been shown to express members of this signal transduction pathway (Hoek et al, 2004;Haass and Herlyn, 2005;Moriyama et al, 2006;Nishikawa and Osawa, 2007). In vivo analyses have revealed that disruption of the Notch pathway in the melanocyte lineage, by either deleting Notch1 and Notch2 receptors (Schouwey et al, 2007;Kumano et al, 2008), or the transcription factor RBP-Jk (Moriyama et al, 2006;Aubin-Houzelstein et al, 2008), results in a precocious hair graying caused by the progressive loss of the melanocyte population. Hence, RBP-Jk-dependent Notch signaling (Schouwey et al, 2010) is required for maintenance of melanoblasts and melanocyte stem cells, and thus to ensure proper hair pigmentation in mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mice with a conditional deletion of RBP-J R (Notch transcription mediator) display, soon after birth, impaired hair pigmentation and subsequent progression of hair graying. Specifically, Notch1 and Notch2 targeted deletion in melanocytes led to inactivation of the RBP-J R gene in a dose-dependent manner, and three intact alleles of Notch1 and Notch2 are required for preventing precocious hair graying [98]. Notch 3 and 4 are not implicated in this phenotype [99,100].…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 99%
“…It was also reported that Notch signaling, via its target gene Hes1, is essential for the maintenance of melanoblasts and adult melanocyte stem cells [97,98]. Moreover, mice with a conditional deletion of RBP-J R (Notch transcription mediator) display, soon after birth, impaired hair pigmentation and subsequent progression of hair graying.…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 99%
“…Both Notch 1 and Notch 2 signalling pathways are required for the maintenance of melanoblasts and melanocyte stem cells and are essential for proper hair pigmentation in mice [38]. Premature greying of hair has been shown to significantly predispose one for CAD less than 35 years of age [39].…”
Section: Aetiopathogenesismentioning
confidence: 99%